International Labour Standards as a Factor for Overcoming the Socio-Economic Consequences of the COVID-19 Pandemic - Staykov, Ivaylo (Research Papers, 2021)
The research is dedicated to the role of The International Labour Organization in overcoming the COVID-19 pandemic and its long-term socio-economic consequences. It examines the applicable international labour standards in times of crisis, including the COVID-19 pandemic.